Electronically controlled radiation pattern leaky wave antenna array for (C band) application - Mowafak K. Mohsen; M. S. M. Isa; Z. Zakaria; A. A. M. Isa; M. K. Abdulhameed; Mothana L. Attiah; Ahmed M. Dinar (Universitas Ahmad Dahlan, 2019)
This paper provides an insight of a new, leaky-wave antenna (LWA) array. It holds the ability to digitally steer its beam at a fixed frequency by utilizing only two state of bias voltage. This is done with acceptable impedance matching while scanning and very little gain variation. Investigation is carried out on LWAs’ control radiation pattern in steps at a fixed frequency via PIN diodes switches. This study also presents a novel half-width microstrip LWA (HWMLWA) array. The antenna is made up of the following basic structures: two elements and reconfigurable control cell with each being comprised of two diodes and two triangle patches. A double gap capacitor in each unit cell is independently disconnected or connected via PIN diode switch to achieve fixed-frequency control radiation pattern. The reactance profile at the microstrip’s free edge and thus the main beam direction is changed once the control-cell states are changed. The main beam may be directed by the antenna between 61o and 19o at 4.2 GHz. C band achieved the measured peak gain of the antenna of 15 dBi at 4.2 GHz beam scanning range.